Back Cover: Stable, Reactive, and Orthogonal Tetrazines: Dispersion Forces Promote the Cycloaddition with Isonitriles (Angew. Chem. Int. Ed. 27/2019). Issue 27 (7th June 2019) - Tu, Julian; Svatunek, Dennis; Parvez, Saba; Liu, Albert C.; Levandowski, Brian J.; Eckvahl, Hannah J.; Peterson, Randall T.; Houk, Kendall N.; Franzini, Raphael M.
Abstract : Highly stable tetrazines that react rapidly with isonitriles are presented by R. M. Franzini et al. in their Communication on page 9043 ff. Bulky tetrazine substituents sterically attract the isocyano group in the cycloaddition transition state and block the approach of strained alkenes. These characteristics enable rapid bioorthogonal labeling and release reactions and allow for triple‐orthogonal protein labeling.